Toxicity and risks with T-2 and HT-2 toxins in cereals. - Pettersson, H. (Plant Breeding and Seed Science, 2011)
The trichothecenes T-2 and HT-2 toxins have during recent years been found frequently in cereals grown in Europe. They are mainly produced by Fusarium langsethiae. High concentrations of the toxins are most commonly found in oats, but they are also detected frequently at lower concentrations in barley. Wheat is only rarely contaminated. Yearly surveys of T-2 and HT-2 toxins in oats from Northern Europe have shown that the occurrence and levels have increased from 2002, with very high levels in 2005-2007, followed by a decrease in 2008-2009. Raw oats delivered to mills for processing to food have also been highly contaminated with T-2 and HT-2 toxins during the period 2006-2009. The processing of oats in the mills by sorting-sieving and dehulling reduce the toxin concentrations in the final food products, flakes and meals, with more than 80 % even at high levels in the raw oat. The concentrations of the toxins in the by-products from the process are instead increased. The by-products are mainly used as feed components. The toxic effects of T-2 and HT-2 toxins in animals and the toxicological information used in the risk evaluations are briefly described. Risk evaluations of the toxins in cereals for human consumption have been conducted by both EU-Scientific Committee on Food and by JECFA in 2001. Both evaluations resulted in the same temporary tolerable daily intake (t-TDI) for the sum of T-2 and HT-2 toxins. The group TDI for T-2 and HT-2 toxins, alone or in combination, became 60 ng/kg bw and day. The intake of T-2 and HT-2 toxins through oats is calculated from median concentrations in oat products and median consumption data from Norway. The intake was found to be 1.5-5.4 % of the t-TDI. The toxic effects studied or expected in farm animals, horses and ruminants, consuming high amounts of oat in their feed are described and discussed.